GRADUATE ON TIME MONITORING SYSTEM (GoTMS): THE DEVELOPMENT OF POSTGRADUATE STUDY PROGRESS MONITORING SYSTEM - Norizzati Muhamad Sofi; Mazida Ahmad; Shri Dewi Applanaidu; Massudi Mahmuddin; Sabrina Ahmad (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Abstractâ€” Graduate on time (GoT) has become one of the important factors among postgraduate (PG) students. The Graduate on Time Monitoring System (GoTMS) is a sub-system designed for the School of Economics, Finance and Banking (SEFB), Universiti Utara Malaysia to monitor students’ progress. The study aims to design and develop a monitoring system for post graduate students. In addition, GoTMS enhancement included some features that can store computerized data to replace the manual method that is difficult for the staff to store many data efficiently at the office. Hence, the stored computerized data and automated monitoring that comes from the reminder message function of GoTMS can completely change the way of data management and can observe postgraduate progression to graduate on time easily. The method used to develop the GoTMS is based on the Project Management Process, which covers every aspect of developing this system from the Project Initiation, Project Planning, Project Execution, Monitoring & Controlling, and Project Closing states. In the process of design and development of GoTMS, the Software Development Life Cycle (SDLC) Waterfall approach involved starting with identifying the requirements, code writing, and design, testing the code before releasing it to users, and monitoring the process before closing and evaluating it to produce a final report. The outcome for this proposed work was a high-fidelity prototype of GoTMS system was developed and undergo usability testing to SEFB experts and targeted users of the system to obtain feedback and comments on the system prototype, which is based on four main components: usefulness, ease of use, satisfaction, and security provided by GoTMS. Staff and post graduate students were the respondent for usability testing of GoTMS. As a result, respondents have expressed hope to implement this system as it will contribute to them in ensuring postgraduate students graduate on time.